Stanowienie oraz stosowanie polityki ekologicznej przez administrację publiczną w Polsce oraz Unii Europejskiej - Maciej Jabłoński (Studia Ecologiae et Bioethicae)
Environmental protection is a field of law about interdisciplinary character, which using notions typical of legal, natural, technical, or chemical theories is a rule in. Therefore in practice, they can have the notional various meaning depending on the context they stayed in which used. A notion which is paying attention to the rights and duties of citizens, bodies of a public authority or also environmental organizations, is an ecological politics.